Vicissituds del tresor de la catedral de Lleida i els inventaris del segle XIV = Vicissitudes of the Lleida cathedral treasury and the 14th-century inventories - Llevot, Francesc Fité i (Miscel·lània litúrgica catalana, 2024)
In this study, we offer a vision of the vicissitudes suffered by the treasury of the cathedral of Lleida, going on to focus on the only two inventories remaining from the 14th century.